ASYMMETRICAL OCULAR DERMOID IN NATIVE KOREAN CATTLE - Y.S. Roh; D.B. Gi; C.W. Lim; B. Kim (Journal of Animal and Plant Sciences, 2014)
This paper describes two cases of ocular dermoids in native Korean cattle based on gross and histopathologic findings. In Case 1, the choristoma on the left side was characterized by hair growth in the cornea conjunctiva, while the choristoma on the right side was only located in the nictitans. The choristoma in Case 2 was located in the left cornea conjunctiva. The choristomas were surgically excised from the ocular area. Histopathologically, hair shafts, hair bulbs, and sebaceous and sweat glands were observed in the epidermis and dermis of the choristoma. Based on the anatomical location and histopathological features of the masses with hair, each choristoma in Case 1 was diagnosed as a bilateral, corneoconjunctival and conjunctival dermoid, and the one in Case 2 was diagnosed as a unilateral, corneoconjunctival dermoid. The bilateral coexistence of two different types of ocular dermoids in one individual has not been previously reported.
Keywords: Ocular dermoid; choristoma; native Korean cattle